Kernohan's Notch: A Forgotten Cause of Hemiplegia—CT Scans Are Useful in This Diagnosis. (20th November 2013) - Panikkath, Ragesh; Panikkath, Deepa; Lim, Sian Yik; Nugent, Kenneth
Abstract : Hemiparesis ipsilateral to a cerebral lesion can be a false localizing sign. This is due to midline shift of the midbrain resulting in compression of the contralateral pyramidal fibers on the tough dural reflection tentorium cerebelli. This may result in partial or complete damage to these fibers. Since these fibers are destined to cross in the medulla and innervate the opposite side of the body, this causes hemiparesis ipsilateral to the site of cerebral lesion. Computed tomography (CT) scans have not been used to support the diagnosis of this entity until now. We report a 68-year-old woman with a subdural hematoma who developed ipsilateral hemiparesis without any other explanation (Kernohan's notch). The CT of the head showed evidence of compression of the midbrain contralateral to the hematoma and was useful in the diagnosis. The purpose of this report is to increase the awareness of this presentation and to emphasize the utility of CT scans to support the diagnosis.